The histology of the alimentary canal and associated structures of Metopolophium dirhodum (Homoptera: Aphididae) - Campbell, M. B. S. C. (Mark Bryer St Clair) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 1985.